Survei Tingkat Kepuasa Pengunjung - Arif - Budiman; Anton Komaini (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
The problem in this study is the absence of an overview of the level of visitor satisfaction with infrastructure and recreational sports tourism services on the beach of Sweet Water in Padang City. This study aims to obtain data, information and description of the level of visitor satisfaction with infrastructure and recreational sports tourism services in the sweet water coast of Padang city. This type of research is descriptive research. This research was conducted on January 17-21 2019 at the sweet water beach of Padang city. The population in this study were all visitors who came to the sweet water beach of the city of Padang, including students, students, bodyguards, general and others. The sample in this study was taken by the technique of Convenience Or Accidental Sampling (accidental sample), where each visitor who came to the sweet water beach of Padang city had the opportunity to become a sample, in this study a sample of 100 visitors. Of the 100 visitors it was divided into five parts, namely 20 paragliding, 20 hangers, 20 surfing, 20 flying fox, and 20 ATVs. The results showed that the level of visitor satisfaction with infrastructure and recreational sports tourism services in the sweet water coast of Padang city was included in the strong category with a percentage of 71%. These results include: 1) Reliability factors, categorized as strong with a percentage of 71%, 2) Resvonsiveness factors, categorized as strong with a percentage of 69%, 3) Guarantee factors, categorized as strong with a percentage of 73%, 4 ) Empathy factors (empathy) are categorized as strong with a percentage of 71%, 5) Factors of physical evidence (tangibles): a) Paragliding, categorized as very strong with a percentage of 83%, b) Cantilever, categorized as strong with a percentage of 70%, c) Surfing, categorized very strong with a percentage of 83%, d) Flying Fox, categorized as strong with a percentage of 69%, e) ATVs, categorized as strong with a percentage of 76%.